DETERMINANTS OF HOME ENVIRONMENTAL HEALTH RELATED TO PULMONARY TUBERCULOSIS SCORE IN THE WORKING AREA OF UPTD JOHAN PAHLAWAN PUBLIC HEALTH CENTER - Cut Fidha Balkis; Mardi Fadillah; Ernawati; T.M Rafsanjani (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
This study aims to analyze the relationship between determinants of home environmental health, including ventilation, lighting, residential density, temperature and humidity, and home sanitation with the incidence of Pulmonary Tuberculosis in the working area of the Johan Pahlawan Community Health Center (UPTD). The research method uses a quantitative approach with a correlational design. The study population is households that have family members with pulmonary TB based on the Puskesmas medical records, with a sample of 50 respondents determined using a purposive sampling technique . Data were collected through questionnaires and home observations, then analyzed using descriptive statistical tests, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the help of SPSS software version 26. The results of the study indicate that residential density has a positive and significant effect on the incidence of pulmonary TB, while home sanitation has a negative and significant effect on the incidence of pulmonary TB. Meanwhile, ventilation, lighting, and temperature and humidity do not show a statistically significant relationship with the incidence of pulmonary TB. The conclusion of this study confirms that residential density and home sanitation are the main determinants of the incidence of pulmonary TB, so that prevention efforts based on improving the home environment are needed to reduce the risk of pulmonary TB transmission in the community.